Associations between depression and parenting of fathers in Head Start and parental self-efficacy as a protective factor. (January 2021) - Chung, Gerard; Smith, Quinton; Frey, Joseph; Lanier, Paul
Highlights: Prevalence of depression among fathers in Early Head Start/Head Start programs. Fathers' depression weakens relationship closeness with their children. Depression increases relationship conflicts with their children. Parental self-efficacy mitigates the influence of depression. Improving fathers' parental self-efficacy is important in early childhood services. Abstract: Head Start/Early Head Start (HS/EHS) programs deliver comprehensive early childhood services in the U.S. to support low-income families to improve a range of early childhood outcomes and to develop positive parenting and parent-child relationships. From the beginning of the program, increasing fathers' involvement with their children in HS/EHS has been an important emphasis. However, depressive symptoms among low-income fathers can negatively impact their relationships with their children. Protective factors such as parental self-efficacy (PSE) can potentially buffer the effects of depression. In this study, we aimed to understand the associations between low-income HS/EHS fathers' depressive symptoms and relationship closeness and conflict with their young children aged 5 and below. We also examined if the PSE of fathers can buffer the negative associations between depression and father-child relationship. We analyzed cross-sectional data collected from fathers ( n  = 102) who participated in a parenting support program while receiving HS/EHS services in the United States. Participants were primarily African American (83%), of mean age 32 years, and lived with their children (74%). Using multiple linear regression, we found that fathers' depression was significantly associated with father-child closeness ( B  = −0.37, p  < .001) and conflict ( B  = 0.28, p  < . 05). More importantly, PSE functioned as a protective factor by reducing the negative associations between depression and fathers' relationship closeness and conflict with their children. Implications include providing mental health assessments and support to low-income fathers. HS/EHS services or early childhood services that aim to promote positive parenting practices and develop healthy parent-child relationships among low-income fathers should give attention to strengthening PSE in fathers.